Music and Dementia 2019
DOI: 10.1093/oso/9780190075934.003.0002
|View full text |Cite
|
Sign up to set email alerts
|

Is Music Special for People With Dementia?

Abstract: Multitudes of studies support that musical interventions in people with dementia positively affect various domains of their well-being—emotional, cognitive, and behavioral—and also reduce the distress of caregivers. However, the mechanisms underlying these effects remain unclear. This chapter proposes that rhythmic entrainment induced by listening to music, including movements synchronized with musical rhythms, might contribute to the efficacy of music-based interventions for people living with dementia. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

6
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 3 publications
0
9
0
1
Order By: Relevance
“…Some studies demonstrated that active interventions, during which patients are encouraged to sing or move with the musical beats, provide larger benefits than passive ones whereby patients only listen to music without motor incentive 3,4 . This finding suggests that the ability to synchronize movements with a musical rhythm, which is relatively spared in patients with NCD, may contribute to the positive impact of these interventions on patients’ behavior and well‐being 5,6 . Consequently, designing efficient musical interventions requires a better understanding of the change in rhythmic abilities and emotional responsiveness to music with the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies demonstrated that active interventions, during which patients are encouraged to sing or move with the musical beats, provide larger benefits than passive ones whereby patients only listen to music without motor incentive 3,4 . This finding suggests that the ability to synchronize movements with a musical rhythm, which is relatively spared in patients with NCD, may contribute to the positive impact of these interventions on patients’ behavior and well‐being 5,6 . Consequently, designing efficient musical interventions requires a better understanding of the change in rhythmic abilities and emotional responsiveness to music with the severity of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Les quelques études qui ont comparé l'efficacité de ces différentes activités sur le comportement des patients ont montré que les bénéfices de ces interventions étaient plus importants lorsque les patients étaient engagés au niveau moteur dans l'activité musicale (en chantant par exemple) plutôt que lorsqu'ils écoutaient passivement la musique [12,13]. Il se pourrait alors que la stimulation motrice et les interactions sociales jouent un rôle clé dans les bénéfices émotionnels, sociaux et cognitifs de ces interventions, en particulier en promouvant la coordination interpersonnelle [14][15][16].…”
Section: Introductionunclassified
“…This spontaneous interpersonal synchronization, called motor entrainment or alignment, has been observed in laboratory studies, in which dyads of participants unconsciously or voluntarily synchronized their finger tapping (Oullier, Guzman, Jantzen, Lagarde, & Kelso, 2008), their steps while walking side by side (van Ulzen, Lamoth, Daffertshofer, Semin, & Beek, 2008) or the rhythm of rocked chairs sways (Richardson, Marsh, Isenhower, Goodman, & Schmidt, 2007). We can therefore propose that interpersonal synchronization of rhythmic movements might provide relevant indexes to measure patients' engagement with others in a musical context (Ghilain, Schiaratura, Singh, Lesaffre, & Samson, 2019). In addition, the synchronization of individuals' posture, gestures, facial expression and eye gaze, which have long been regarded as the regulators of social interaction, are notably important for the development of rapport and personal relationships (Lakin, Jefferis, Cheng, & Chartrand, 2003).…”
Section: Methodological Aspects Related To the Impact Of Musical Intervention In Patients With Admentioning
confidence: 76%